Model and long-term coherent accumulation basic algorithm for the reflected signal with non-zero higher derivative range to radar target - Kozlov, S. V.; Cuong, Le Van (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
The purpose of the work was to substantiate a mathematical model of the signal reflected from moving radar target at the time of its observation, which determines the need to take into account the range migration and its derivatives up to the third order, inclusive, and the Doppler frequency migration, and the basic algorithm of long-term coherent accumulation for the reflected signal. The algorithm provides for the calculation of the “fast” spectra samples, within each repetition period, time, the phase alignment of the spectra samples by multiplying by the correcting phase factors determined by the expected parameters of the target movement and the number of the repetition period, the summation of the spectral samples in the “slow” time, the multiplication of the result by complex frequency response of a matched filter of a single signal and performing an inverse Fourier transform. The performance of the algorithm is illustrated by the results of computer simulation.